TATALAKSANA BEDAH MIXOMA ODONTOGENIK PADA MANDIBULA : LAPORAN KASUS LANGKA - Sulakso, Tito; Hardianto, Andri; Priyanto, Winarno (Universitas Baiturrahmah, 2024)
Introduction: Odontogenic myxoma is a rare benign odontogenic tumour. Although it grows slowly, odontogenic myxoma is aggressive and has a high recurrence rate after surgical intervention. The tumour is most commonly found in the posterior mandible and is more common in females than in males. Radiographically, odontogenic myxoma presents as a unilocular or multilocular radiolucency with irregular or scalloped borders, frequently accompanied by displacement of teeth in the vicinity of the tumour. The treatment of odontogenic myxoma may be either conservative or radical surgery. Case and Management: A 57-year-old female patient presented with a palpable mass on the lower jaw that had been growing for a period of two years, accompanied by pain and displacement of the lower teeth. A clinical examination revealed the presence of a hard, non-painful, non-bleeding lump with approximate dimensions of 6x5x4 cm on the mandible, accompanied by displacement of the anterior lower teeth. An incisional biopsy led to the diagnosis of an odontogenic myxoma in the left mandibular region. The patient subsequently underwent surgery comprising segmental resection and plate reconstruction. Conclusion: Odontogenic myxoma is a rare odontogenic tumour with a high recurrence rate. In such cases, segmental resection with a margin of ≥ 1 cm and mandibular reconstruction with a plate is considered the treatment of choice.